Age-Related Dynamics of Circulating Innate Lymphoid Cells in an African Population - Darboe, Alansana; Nielsen, Carolyn M.; Wolf, Asia-Sophia; Wildfire, Jacob; Danso, Ebrima; Sonko, Bakary; Bottomley, Christian; Moore, Sophie E.; Riley, Eleanor M.; Goodier, Martin R. (Frontiers in Immunology, 2020)
Innate lymphoid cell (ILC) lineages mirror those of CD4+ T helper cell subsets, producing type 1, 2 and 3 cytokines respectively. Studies in adult human populations have shown contributions of non-cytotoxic ILC to immune regulation or pathogenesis in a wide range of diseases and have prompted investigations of potential functional redundancy between ILC and T helper cell compartments in neonates and children. To investigate the potential for ILC to contribute to immune responses across the human lifespan, we examined the numbers and frequencies of peripheral blood ILC subsets in a cohort of Gambians aged between 5 and 73 years of age. ILC2 were the most abundant peripheral blood ILC subset in this Gambian cohort, while ILC1 were the rarest at all ages. Moreover, the frequency of ILC1s (as a proportion of all lymphocytes) was remarkably stable over the life course whereas ILC3 cell frequencies and absolute numbers declined steadily across the life course and ILC2 frequencies and absolute numbers declined from childhood until the age of approx. 30 years of age. Age-related reductions in ILC2 cell numbers appeared to be partially offset by increasing numbers of total and GATA3+ central memory (CD45RA-CCR7+) CD4+ T cells, although there was also a gradual decline in numbers of total and GATA3+ effector memory (CD45RA-CCR7-) CD4+ T cells. Despite reduced overall abundance of ILC2 cells, we observed a coincident increase in the proportion of CD117+ ILC2, indicating potential for age-related adaptation of these cells in childhood and early adulthood. While both CD117+ and CD117- ILC2 cells produced IL-13, these responses occurred predominantly within CD117- cells. Furthermore, comparison of ILC frequencies between aged-matched Gambian and UK young adults (25–29 years) revealed an overall higher proportion of ILC1 and ILC2, but not ILC3 in Gambians. Thus, these data indicate ongoing age-related changes in ILC2 cells throughout life, which retain the capacity to differentiate into potent type 2 cytokine producing cells, consistent with an ongoing role in immune modulation.